Method to Biomonitor the Cooked Meat Carcinogen 2‑Amino-1-methyl-6-phenylimidazo[4,5‑b]pyridine in Dyed Hair by Ultra-Performance Liquid Chromatography–Orbitrap High Resolution Multistage Mass Spectrometry - Guo, Jingshu; Yonemori, Kim; Le Marchand, Loïc; Turesky, Robert J (Analytical chemistry (Washington), 2015)
2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) is a carcinogenic heterocyclic aromatic amine formed in cooked meat. The use of naturally colored hair containing PhIP can serve as a long-term biomarker of exposure to this carcinogen. However, the measurement of PhIP in dyed hair, a cosmetic treatment commonly used by the adult population, is challenging because the dye process introduces into the hair matrix a complex mixture of chemicals that interferes with the measurement of PhIP. The high-resolution scanning features of the Orbitrap Fusion mass spectrometer were employed to biomonitor PhIP in dyed hair. Because of the complexity of chemicals in the hair dye, the consecutive reaction monitoring of PhIP at the MS3 scan stage was employed to selectively remove the isobaric interferences. The limit of quantification (LOQ) of PhIP was 84 parts-per-trillion (ppt) employing 50 mg of hair. Calibration curves were generated in dyed hair matrixes and showed good linearity (40–1000 pg PhIP/g hair) with a goodness-of-fit regression value of r 2 > 0.9978. The within-day (between-day) coefficients of variation were 7.7% (17%) and 5.4% (6.1%), respectively, with dyed hair samples spiked with PhIP at 200 and 600 ppt. The levels of PhIP accrued in dyed hair from volunteers on a semicontrolled feeding study who ingested known levels of PhIP were comparable to the levels of PhIP accrued in hair of subjects with natural hair color. The method was successfully employed to measure PhIP in nondyed and dyed hair biospecimens of participants in a case-control study of colorectal adenoma on their regular diet.